The effect of macroeconomics variables to Net Asset Value (NAV) growth of sharia mutual funds in Indonesia - Ardhani, Intan Aulia; Effendi, Jaenal; Irfany, Mohammad Iqbal (Jurnal Ekonomi & Keuangan Islam, 2020)
Purpose – This study aims to perform the short-term and long-term relationships between net asset value of Islamic mutual funds within macroeconomic variables, to analyze responses towards the economic shock, and to analyze the composition of the net asset value of Islamic mutual funds within selected macroeconomic variables. Methodology – Monthly data over the 2015-2019 period were analyzed using the Vector Error Correction Model (VECM), impulse response test, and variance decomposition test. Findings – The results show that inflation, money supply, and gross domestic products had a positive and significant effect on the net asset value of Islamic mutual funds, on the other hand, the rupiah exchange rate had a negative thus insignificant effect on the net asset value of Islamic mutual funds. Research limitation/implication – The main limitation of this research is the lack of a variable that represents the Islamicity index, which can differentiate the driven factors of FDI in Muslim and non-Muslim organization countries. Practical implication – This study suggests that the society and the government should collaborate to maintain the stability of the rupiah exchange rate by buying domestic products, strengthening the real sector. Originality – Here we provide an update data of macroeconomics variables dynamics (e.g. GDP, inflation, exchange rate, and money supply) and its implication to Islamic mutual funds – i.e. net asset value over 2015-2019. We used a novel timeseries analytical approach (VECM) to estimate the magnitude of macroeconomics effects to Islamic mutual funds in Indonesia.